Pengembangan Perangkat Penilaian Autentik Berbasis Kurikulum 2013 Pada Mata Pelajaran IPA/Biologi di Sekolah Menengah Pertama - Sitompul, Putri Handayani; Syarifuddin, Syarifuddin (Magister Pendidikan Biologi, Universitas Negeri Medan, 2017)
This study aims to know feasibility device authentic assessment based Kurikulum 2013 developed in the subject IPA/Biologi in the Junior High School at class VII (seven). The research is research and development using Borg and Gall model. Stage research methodology consisting of : (1) validation of evaluation learning expert, (2) validation of material learning biology expert, (3) individual trial, (4) small group trial, and (5) large group trial. The subject trial consisting of two evaluation learning expert, two material learning biology expert, one teacher for individual trial, three teacher for small group trial, and six teacher for large group trial. Value about the quality of the product development is collected by questionnaire and analyzed with quantitative analysis techniques deskriptive. The result showed: (1) evaluation learning experts are very well qualifications (89,65%), (2) material learning biology expert are very well qualifications (94%), (3) individual trials are in very well qualifications (89,72%), (5) small group trials are in very well qualifications (93,72%), and (6) large group trial are in very good qualifications (97,32%). Based on data analysis It was concluded that the average for validation of evaluation expert, material learning biologu expert, individual trial, small group trial, dan large group trial are very well qualification (91,%).